2021
DOI: 10.1111/evo.14221
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity reveals hidden fish phenotypes and enables morphospace diversification

Abstract: The establishment of a given phenotype is only one expression from a range of hidden developmental possibilities. Developmental plasticity at hidden reaction norms might elicit phenotypic diversification under new developmental environments. Current discussion benefits from empirical analyses that integrate multiple environmental stimuli to evaluate how plastic responses may shape phenotypic variation. We raised Megaleporinus macrocephalus fish in different environmental settings to address contributions of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…This is not surprising, considering that the floral forms of this polyphenic species switch between two extremes (G omez et al, 2020). Plasticity-mediated movements across the morphospace have been reported for several other organisms (Pfennig, 2021), like fish (Muschick et al, 2011;Lofeu et al, 2021), ants (Oettler et al, 2019), nematodes (Susoy et al, 2015) and even plants (Barnett et al, 2018). Our case is remarkable because, in contrast to the findings of b) Floral disparity between each of the two phenotypes (i.e.…”
Section: Plastic Floral Divergence In M Arvensissupporting
confidence: 47%
See 1 more Smart Citation
“…This is not surprising, considering that the floral forms of this polyphenic species switch between two extremes (G omez et al, 2020). Plasticity-mediated movements across the morphospace have been reported for several other organisms (Pfennig, 2021), like fish (Muschick et al, 2011;Lofeu et al, 2021), ants (Oettler et al, 2019), nematodes (Susoy et al, 2015) and even plants (Barnett et al, 2018). Our case is remarkable because, in contrast to the findings of b) Floral disparity between each of the two phenotypes (i.e.…”
Section: Plastic Floral Divergence In M Arvensissupporting
confidence: 47%
“…Several studies have shown that plasticity may cause the colonization of unfilled regions of the morphospace, contributing to the emergence of morphological novelties (Muschick et al, 2011;Levis et al, 2018;Lofeu et al, 2021). In our case, because Brassicaceae floral morphospace is dense and does not have many empty regions, plasticity allowed M. arvensis to colonize a region of the morphospace already occupied by other species.…”
Section: Plasticity-mediated Floral Convergencementioning
confidence: 62%
“…A recent macroevolution study of Characiformes detected a shift to higher speciation rates at the base of the Anostomidae that may have contributed to high levels of modern species diversity in the family [5]. This is also supported by extreme phenotypic plasticity that may have potentialized family speciation processes [81]. Indeed, molecular investigations have found several independent lineages inside Megaleporinus conirostris, M. macrocephalus, M. obtusidens, M. piavussu, M. trifasciatus [38], Laemolyta taeniata [33], Schizodon nasutus, S. vittatus [82], and within the Leporinus desmotes and L. friderici complexes [34,83].…”
Section: Discussionmentioning
confidence: 97%
“…To date, comparable work on the drivers of individual phenotypic variation in fish have tended to focus on one or a few specific environmental axes (e.g., Colosimo et al. 2005 ; Lofeu et al. 2021 ; Ronco et al.…”
Section: Using Neon To Understand the Individual Organism In Its Envi...mentioning
confidence: 99%